STUDENTS’ PERCEPTION OF DIGITAL STORYTELLING TO IMPROVE SPEAKING SKILL AT AN INDONESIAN ISLAMIC HIGHER EDUCATION - Sahril; Munir, Nurasia; Munir, Bayanuddin (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Palu, 2023)
Digital storytelling is a method that combines the art of storytelling with digital media in various forms such as videos, images, text, and so on. Digital storytelling integrates technology into the classroom to facilitate the learning process. Especially in English language learning, this method supports the improvement of students' English language skills. This study aims to identify students' perceptions of digital storytelling to improve students' speaking skills at an Indonesian Islamic college. This mixed-method study involved 30 second-semester students at Datokarama State Islamic University in Palu. Quantitative data using questionnaires were analysed based on percentages while qualitative data in the form of interviews were analysed with three stages, namely, data reduction, display, and verification. Five aspects of perception are of concern in this study, namely attitude, motivation, interest, experience, and expectations. The research results from the five aspects prove that students have a positive perception of the use of digital storytelling in improving their speaking skills. Digital storytelling makes it easier for students to understand the material well, gives them confidence in interacting and cooperating in the classroom, and creates a fun learning process.